لوجستيات النقل البري وترقية صادرات المنتجات الفلاحية الجزائرية - زيادي, عادل; زيات, عادل (جامعة الوادي - University of Eloued, 2021)
The present paper aims to shade the light on the reality of agricultrual products and presents the reality of logistic transportation in the international indicators. We used a descriptive method to present the different aspects of logistics and we used an analytic one concerning exports and the logistics performance index data. The research argues that the majority of Algerian exports transported by land tothe south or Tunisia or Libya or Mauritania are fuel or building materials. It also argues that the promotion of agricultural exports of Algeria to African countries by truck transportation relies on the modernization of Logitrans company. The modernization can occur by the use of ICT in the practice of their activities, the exploitation of research results issued by universities and by establishement of a direct link between the agricultural producer and the transportation firm.
Truck Transportaion Logistics and the Promotion of Algerian Agricultural Products Exports
مقال
Keywords: لوجستيك ; الصادرات الفلاحية ; النقل البري ; المنتجات الزراعية